FASILITAS PENDUKUNG DALAM PEMBANGUNAN PARIWISATA KABUPATEN LOMBOK UTARA PROVINSI NUSA TENGGARA BARAT - Siti Atika Rahmi (Universitas Tribhuwana Tunggadewi, 2017)
Abstract: Development of tourism as part of local government effort in managing regional potency to improve prosperity of society around tourist destinations and society in general, which require supporting facilities. This research is part of dissertation research entitled Development of Tourism Based on Local Wisdom in Context of Regional Development (Study at Tourism Office of North Lombok Regency, West Nusa Tenggara). The focus in this article discusses the supporting facilities in the development of tourism North Lombok regency. The research method used qualitative approach, collecting data through observation, interview, secondary study giving general description about the condition of tourism and its development in North Lombok Regency (Kabupaten Lombok Utara) West Nusa Tenggara Province (Provinsi Nusa Tenggara Barat). The respondents identification using purposive sampling. Testing the validity of data in this study include test credibility (internal validity), transferability (external validity), dependability (reliability), and confirmability (objectivity). The results showed that in general the supporting facilities owned by North Lombok Regency of West Nusa Tenggara already meet the standards and needs of tourists. Keywords: Supporting Facilities, Development, Tourism.